Analisis Faktor-Faktor Yang Mempengaruhi Penerimaan Opini Audit Going Concern Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek IndonesiaTahun 2011-2014 - Sya'baini, Imam Nugroho, Fauzan, S.E, M.Si, Ak (2016)
Going concern audit opinion is the opinion issued by the auditor to determine whether the company can maintain its viability. Going concern audit opinion can be used as an early warning for the users of the financial statements in order to avoid mistakes in decision-making. This study aims to examine the analysis of the factors that affect the likelihood of the company receiving going concern audit opinion. Factors tested in this study is the financial condition, quality audit, debt default, the audit opinion the previous year, and the size of the company. This study uses the manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2011-2014. Samples were obtained by purposive sampling. Data were analyzed using logistic regression analysis . Results of the study is the financial condition, quality audit, and the size of the company does not affect the going concern audit opinion. While debt default and the previous year's audit opinion affect the going concern audit opinion.